Solving Advanced Argumentation Problems with Answer-Set Programming - Brewka, Gerhard; Diller, Martin; Heissenberger, Georg; Linsbichler, Thomas; Woltran, Stefan (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
Powerful formalisms for abstract argumentation have been proposed. Their complexity is often located beyond NP and ranges up to the third level of the polynomial hierarchy. The combined complexity of Answer-Set Programming (ASP) exactly matches this complexity when programs are restricted to predicates of bounded arity. In this paper, we exploit this coincidence and present novel efficient translations from abstract dialectical frameworks (ADFs) and GRAPPA to ASP.We also empirically compare our approach to other systems for ADF reasoning and report promising results.